Integration of a Capacitive EIS Sensor into a FIA System for pH and Penicillin Determination - Michael J. Schöning; Arshak Poghossian; David Rolka (Sensors, 2004)
Abstract: A field-effect based capacitive EIS (electrolyte-insulator-semiconductor) sensor with a p-Si-SiO2-Ta2O5 structure has been successfully integrated into a commercial FIA (flow-injection analysis) system and system performances have been proven and optimised for pH and penicillin detection. A flow-through cell was designed taking into account the requirement of a variable internal volume (from 12 Î¼l up to 48 Î¼l) as well as an easy replacement of the EIS sensor. FIA parameters (sample volume, flow rate, distance between the injection valve and the EIS sensor) have been optimised in terms of high sensitivity and reproducibility as well as a minimum dispersion of the injected sample zone. An acceptable compromise between different FIA parameters has been found. For the cell design used in this study, best results have been achieved with a flow rate of 1.4 ml/min, distance between the injection valve and the EIS sensor of 6.5 cm, probe volume of 0.75 ml, cell internal volume of 12 Î¼l. A sample throughput of at least 15 samples/h was typically obtained.